The legal and ethical framework for international tissue transfer - Lenk, Christian (Henry Stewart Talks, 2022)
Regulation of tissue research, No-Property-Principle, The Bundle Theory of Property, European Convention on Human Rights and Biomedicine, Commodification of Body Material, Damage by Loss of Material, Double Character of Body Material, Anonymisation and Pseudonymisation of Body Material